Sultan's lost treasure - Sweigart, Stephen; Stiers, David Ogden; Apsell, Paula S. (WGBH Educational Foundation, 2001)
Naval archaeologists excavate the wreck of a 15th-century Chinese junk which sank off the coast of Brunei. The junk's cargo consists of thousands of jars and pieces of porcelain.